Extracellular vesicles are associated with the systemic inflammation of patients with seropositive rheumatoid arthritis (2018)
ABSTRACT: Patients with rheumatoid arthritis (RA) and autoantibodies, such as rheumatoid factor and those against cyclic citrullinated peptides, are designated as seropositive and have a more severe disease with worse prognosis than seronegative RA patients. Understanding the factors that participate in systemic inflammation, in addition to articular commitment, would allow better treatment approaches for prevention of RA comorbidities and disease reactivation. We evaluated whether monocyte subsets and extracellular vesicles (EVs) could contribute to this phenomenon. Seropositive patients had higher levels of proinflammatory cytokines than those of seronegative patients and healthy controls (HCs); however, this systemic inflammatory profile was unrelated to disease activity. High frequencies of circulating EVs positive for IgG, IgM, CD41a, and citrulline, together with altered counts and receptor expression of intermediate monocytes, were associated with systemic inflammation in seropositive patients; these alterations were not observed in seronegative patients, which seem to be more similar to HCs. Additionally, the EVs from seropositive patients were able to activate mononuclear phagocytes in vitro, and induced proinflammatory cytokines that were comparable to the inflammatory response observed at the systemic level in seropositive RA patients; therefore, all of these factors may contribute to the greater disease severity that has been described in these patients.